The Role of CVA Gymnastics Against Increase Functional Ability of Post Cerebro Vascular Accident Patients - Grido Handoko Sriyono; Alwin Widhiyanto; Mariani Mariani (Universitas Aisyah Pringsewu, 2023)
Background Cerebrovascular accident (CVA) has a sudden and severe impact on the blood vessels of the brain. In Indonesia alone, 28.5% of CVA sufferers die and the rest experience paralysis or disability, only 15% can make a full recovery. Cerebrovascular accident (CVA) exercise aims to improve the functional abilities of post-CVA patients. The study aims to determine the difference in the effectiveness of CVA exercise therapy 3 x a week and 4x a week for 12 weeks. Methods The research design used a quasi-experimental approach with a non-random pretest-posttest. The study sample was 44 people who experienced ischemia CVA. data collection using the Barthel Index scale. Results Analysis of data normality with the Shapiro-Wilk test and then paired t-test and Mann-Whitney test. The results of CVA exercise research can improve the functional ability of post-CVA patients with an average increase in CVA exercise 4x and 4x a week is 9.636 (p=0.000) and 10.909 (p=0.000). However, the difference in functional ability improvement between the two groups of participants was not statistically significant (p-value = 0.198). Conclusion CVA exercise can improve the functional abilities of post-CVA patients. Abstrak: Latar belakang Cerebro vascular accident (CVA) memberikan dampak cedera yang berat dan mendadak pada pembuluh-pembuluh darah otak di Indonesia sendiri, 28,5% penderita CVA meninggal dunia dan sisanya mengalami kelumpuhan atau kecacatan, hanya 15 % saja yang dapat sembuh total. Senam cerebro vascular accident (CVA) bertujuan meningkatkan kemampuan fungsional pasien paska CVA. Penelitian bertujuan untuk mengetahui perbedaan efektifitas terapi senam CVA 3 x seminggu dan 4x seminggu selama 12 minggu. Metode Rancangan penelitian menggunakan quasi eksperimen dengan pendekatan non random pretest-posttest. Sampel penelitian 44 orang yang mengalami CVA iskemia. pengumpulan data menggunakan skala Indeks Barthel. Hasil Analisa normalitas data dengan uji Shapiro-wilk, selanjutnya uji t berpasangan dan uji mann whitney. Hasil penelitian senam CVA dapat meningkatkan kemampuan fungsional pasien paska CVA dengan rerata peningkatan pada senam CVA 4x dan 4x seminggu adalah 9,636 (p=0,000) dan 10,909 (p=0,000). Akan tetapi, perbedaan peningkatan kemampuan fungsional antara kedua kelompok partisipan tersebut secara statistik tidak signifikan (p value= 0,198). Kesimpulan Senam CVA dapat meningkatkan kemampuan fungsional pasien paska CVA.